Gender justice paradox: Women in management positions in science and technological institutions in the central zone of Mexico - Sanchez-Cruz, E.; Masinire, A.; Gerónimo-Vázquez, C. (South African Journal of Higher Education, 2020)
The past fifty years have witnessed intense local and international gender equity activism. However, the gender landscape has not transformed significantly to reflect a gender equal and just space. Men continue to occupy top influential political and economic positions. While current theoretical work on gender has developed incisive analytic tools which problematise gender essentialism, normative gender stereotypes persist and continue to dominate the institutional practices in many management positions in technological institutions in Mexico. The purpose of this study was to interrogate gender representation in key management positions in the state technological institutes of the central zone of Mexico. We analysed employment and recruitment documents available on the national database and compared the statistics on gender lines to establish the percentage of male and female managers in the science and technological institutes. The results showed that a greater proportion of management positions were occupied by men who were underqualified academically and professionally. Though there were few women in these posts, those women had appropriate and relevant qualifications. We conclude that gender difference may be used to explain the gender biased employment practices in key leadership positions in the technological institutes in Mexico. We also suggest possible research, policy and practical implications beyond the borders of Mexico.